Osteoporosis — Are we aware? - Sen ​ Suchandra; Mookerjee Musfiqua (Journal of Pharmaceutical Research)
The number of women with osteoporosis, a condition characterized with reduced bone mass and the disruption of bone architecture is on the rise in India. Deficiency of calcium and low vitamin D levels are important risk factors for the development of osteoporosis. Low sun exposure, inadequate dietary vitamin D intake, lack of food fortification with vitamin D, pigmented skin, environmental pollution, and traditional dress code further aggravate the condition. Age, gender (female), Asian origin, low BMI also act as a threat for the disorder. It is estimated that maximum bone loss occurs in women during perimenopause and menopause, indicating the prevalence of osteoporosis to increase with advancing age, resulting in a geriatric female population prone to fractures and related morbidities. For the proper management of any disorder, it is imperative that the patient should have an understanding of the disease, which begins with awareness. However, owing to societal pressures the elderly Indian female population rarely prioritizes osteoporosis as a major health issue. In the last few decades the life expectancy has increased giving rise to a larger geriatric population. It is necessary to ensure proper health status for this populace, in order to improve their quality of life which will uplift the national health benchmark. The key to effective and compliant therapy is adequate knowledge of the disorder among the target subjects. The current review highlights the prevalence, etiology and awareness of osteoporosis among Indian women. Keywords: Osteoporosis, Indian women, Awareness